1992
DOI: 10.1037/h0078754
|View full text |Cite
|
Sign up to set email alerts
|

Misattribution of dissonance and behaviour-consistent attitude change.

Abstract: Dissonance theorists have speculated that people who have misattributed dissonance arousal to an external .source may come to question the appropriateness of this attribution. Moreover, they may then be motivated to alter their attitudes. The current study tested this latter notion by having an experimenter discredit the plausibility of an external source after misattribution had presumably occurred. Sixty-four female undergraduates were given a pill described as having either unpleasant side effects or no sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…From Beauvois and Joule’s perspectives, these two rationalization processes are mutually exclusive (Gotz-Marchand, Gotz, & Irle, 1974; Simon, Greenberg, & Brehm, 1995) as choosing one of them makes it highly unlikely that the other will also be chosen. Moreover, Joule and Martinie (2008) have put this exclusive switch model of alternate modes of dissonance reduction to the test, using the misattribution paradigm (Fointiat, 1996; Wright, Rule, Ferguson, McGuire, & Wells, 1992; Zanna & Cooper, 1974). Besides this exclusive model of modes of reduction (sometimes referred to as the “all-or-none model”) some researchers support a complementary model (also called “hydraulic model”, Brehm & Cohen, 1962; Fointiat, 1998; Leippe & Eisenstadt, 1994; Stone, Wiegand, Cooper, & Aronson, 1997).…”
Section: Theory Of Rationalization: a Radical Perspective On Cognitive Dissonancementioning
confidence: 99%
“…From Beauvois and Joule’s perspectives, these two rationalization processes are mutually exclusive (Gotz-Marchand, Gotz, & Irle, 1974; Simon, Greenberg, & Brehm, 1995) as choosing one of them makes it highly unlikely that the other will also be chosen. Moreover, Joule and Martinie (2008) have put this exclusive switch model of alternate modes of dissonance reduction to the test, using the misattribution paradigm (Fointiat, 1996; Wright, Rule, Ferguson, McGuire, & Wells, 1992; Zanna & Cooper, 1974). Besides this exclusive model of modes of reduction (sometimes referred to as the “all-or-none model”) some researchers support a complementary model (also called “hydraulic model”, Brehm & Cohen, 1962; Fointiat, 1998; Leippe & Eisenstadt, 1994; Stone, Wiegand, Cooper, & Aronson, 1997).…”
Section: Theory Of Rationalization: a Radical Perspective On Cognitive Dissonancementioning
confidence: 99%
“…It is worth mentioning that Fointiat (1998) showed that if participants in a misattribution situation did not change their attitude, they were found to use another mode of dissonance reduction, namely act rationalization (Beauvois & Joule, 1996, 1999Beauvois, Joule, & Brunetti, 1993;Joule, 1996). Moreover, in misattribution situations attitude change can occur if counterattitudinal behavior is reintegrated (Higgins, Rhodewalt, & Zanna, 1979), or if participants come to question the appropriateness of the misattribution's source (Wright, Rule, Ferguson, McGuire, & Wells, 1992). In sum, participants in misattribution situations experience cognitive dissonance.…”
mentioning
confidence: 96%